Chasing a blond moon - Heywood, Joseph (Heywood, Joseph. Woods cop mystery., 2023)
Strange things are happening to the black bears of the Upper Peninsula. Grady Service is stumped until a Korean-born professor is murdered by cyanide-laced figs containing two freeze-dried bear gallbladders.